Putting Byrnes and Hong Kong in a time machine: human rights in 2021 under the shadow of Beijing's National Security Law. Issue 3 (2nd September 2021) - Deva, Surya
ABSTRACT: During his academic journey in Hong Kong, Professor Andrew Byrnes wrote extensively on various human rights issues in Hong Kong, including the role of the Bill of Rights Ordinance (BORO) in protecting and promoting human rights. When Byrnes left the University of Hong Kong in 2001, a national security law was contemplated, but perhaps not the type of National Security Law (NSL) that Beijing gifted to Hong Kong on 30 June 2020. Drawing on Byrnes' human rights writings about Hong Kong, this article critically examines the impact of the NSL on human rights in Hong Kong protected under the Basic Law and the BORO. It also discusses the role of Hong Kong courts in minimising the adverse impact of the NSL on human rights. I argue that courts should rely on the basic structure doctrine to declare unconstitutional the relevant parts of the NSL. However, as Hong Kong courts may not be willing to opt for such an option, they should at least treat the NSL as a law of 'suspect constitutionality' and interpret its vague and wide provisions narrowly to strike a balance between national security considerations and the protection of human rights.